1993
DOI: 10.1139/v93-265
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of the deprotonation of β-keto esters by cyclodextrins

Abstract: . Can. J. Chem. 71, 2139 (1993). The rates of deprotonation of several P-keto esters in basic aqueous solution are elevated by a -and P-cyclodextrin (a-and P-CD). In most cases saturation kinetics are observed that indicate fairly strong binding of the esters to the CDs (K, = 0.22-1 1 mM); catalytic ratios (k,/k,) are in the range 1.9-17. For esters of the form RCO-CH,COOEt with both a-and P-CD the values of Kd and k,/k, show little sensitivity to the acyl group, RCO (R = Me, Et, Pr, i-Pr), and for 2-carboetho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Enolizations are catalyzed, , as well as aldol condensations , and decarboxylations . Some reports have appeared dealing with free radical reactions within cyclodextrin complexes. , …”
Section: Simple Cyclodextrinsmentioning
confidence: 99%
“…Enolizations are catalyzed, , as well as aldol condensations , and decarboxylations . Some reports have appeared dealing with free radical reactions within cyclodextrin complexes. , …”
Section: Simple Cyclodextrinsmentioning
confidence: 99%
“…From the kinetic studies, it was suggested that the binding of the β-keto esters in the CD cavities, adjacent to a basic oxyanion site, enhances the reactivity of the CD anions toward these weak carbon acids by an order of magnitude of at least 2-4 (Figure 30). 108 Pyrolysis of O-furfuryl S-alkyl dithiocarbamate (xanthates) gave furfuryl alkyl sulfides together with S-alkyl dithocarbamates. This reaction was affected by the polarity of the solvent.…”
Section: Transfer Elimination Isomerization and The Other Reactionsmentioning
confidence: 99%
“…The rate of deprotonation of several β-keto esters in alkaline aqueous solution was increased by using α- and β-CDs. From the kinetic studies, it was suggested that the binding of the β-keto esters in the CD cavities, adjacent to a basic oxyanion site, enhances the reactivity of the CD anions toward these weak carbon acids by an order of magnitude of at least 2−4 (Figure ) 30 The effect of CD on the deprotonation …”
Section: 26 Transfer Elimination Isomerization and The Other Reactionsmentioning
confidence: 99%
“…To distinguish between the modes 1 and 2 , we studied the attack of the anions of TFE and 2-ME on a series of p -nitrophenyl alkanoates (C 2 to C 10 ) in the presence of α-CD, β-CD, and hp-β-CD. 10b, On the basis of previous studies of reactions of alkyl derivatives in the presence of CDs, ,,,, and on the binding of aliphatics to CDs, ,,, we used the sensitivity of kinetic parameters for the CD-mediated reactions to ester chain length to probe for acyl group binding in the transition state. It was found that for short esters (C 2 to C 6 ) the parameters are not sensitive to the acyl chain, but for longer esters they increase strongly with the chain length 10b.…”
Section: Introductionmentioning
confidence: 99%
“…Differences arising from the CD cavity sizes 11 were also of interest since a larger CD cavity might permit partial inclusion of both reactants in the transition state. As previously, the sensitivity of kinetic parameters to chain length would serve as the main criterion of transition state binding, ,,,10b,, along with appropriate comparisons to initial state binding parameters.…”
Section: Introductionmentioning
confidence: 99%